Evapotranspiração de referência no estado do Paraná - Rodrigues, Neiva Sales (2019)
Evapotranspiration (ETo) is the set of two processes: soil evaporation and water bodies and plants transpiration. The study of evapotranspiration is essential to determinate the water balance of a region and the application of methods for estimating losses by evapotranspiration is necessary for the water availability in several regions, such as the quantification of water deficiencies in agricultural crops. ETo can be determined by direct and indirect methods when there are data restrictions at the study site. Thus, this dissertation aimed to estimate the reference evapotranspiration in Paraná state using different methods, as well as to calibrate and evaluate the performance of the Hargreaves method (1985) (HargreavesSamani), in relation to the standard FAO Penman-Monteith method. Daily air temperature (maximum and minimum) and relative humidity (insolation and wind speed) data for 30-year evapotranspiration estimation (available from 1989 to 2018) were obtained from conventional weather stations at the National Institute of Meteorology (INMET) and Paraná Agronomic Institute (IAPAR). Gap filling was carried out of three stations; evapotranspiration was obtained by FAO 54 Penman-Monteith (1998), Makkink (1957), 1985 Hargreaves (Hargreaves-Samani), Priestley-Taylor (1972), FAO 24 Blaney-Criddle and Turc (1961) methods; the HargreavesSamani calibration was obtained by the Nonlinear Generalized Reduced Gradient (NRG) method and the data was validated through statistical analysis. The results indicate good applicability of alternative methods, and the Hargreaves-Samani equation significantly reduced errors after calibration. The analysis of daily evapotranspiration estimation data for the state of Paraná is indicated, and the adjustments of the alternative equations improve the performance of the results.